PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII - Okri, Levira (Departemen Matematika, 2023)
In measuring the level of success of students in understanding the competences or the materials in learning mathematics using the learning outcomes. However, the outcomes of mathematics learning of 8th grader (VIII) students of SMPN 33 Padang are still relatively low. One thing that can be done to solve this challenge is to use a cooperative learning model with type of Student Teams Achievement Division (STAD) in the learning process. The research type used was a quasy experiment with a static group design. The class of research subjects determination was conducted using technique by simple random sampling and then class VIII-6 was chosen as the class for experimental and class VIII-4 as the class for control.The research results shown that the mathematics learning outcomes of students who are taught with model by cooperative learning using the STAD type are better than students who are taught with models by conventional learning. It show that the value in average for the class of experimental was 16,43 and the value in average for the class of control is 13,27. Keywords– Mathematics learning outcomes, Student Teams Achievement Divisio